Memorandum: Erfolgsbedingungen empirischer Wirtschaftsforschung und empirisch gestuetzter wirtschafts- und sozialpolitischer Beratung - Richard Hauser; Gert G. Wagner; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 1998)
Based on the hypothesis that microdata are of crucial importance for internationally competitive economic research and scientific advice in economic and social policy, the authors develop various proposals for an improved data supply for empirical work in Germany. Present shortcomings are mainly caused by a lack of coordination between data collecting institutions and scientific users, extensive privacy protection provisions and restrictive information policy of government agencies. In order to overcome these problems, the authors ask for improved participation of scientific users in data collection; provision of recent techniques for data anonymization and decentralized use of confidential centralized data; liberalization of scientific data access; and creation of a documentation center for organization and standardization of data and data access. Finally, empirical economics, especially application of microdata and modern tools of data analysis, should be emphasized within the framework of university education.
Keywords: C81; C82; 330; microdata; data collection; data access; data organization